Retorika iskrenosti - Hajdu, Péter (Primerjalna književnost, 2004)
The Rhetoric of Sincerity. The impression that a poem is sincere presupposes an intention that coincides with the meaning of the text, while irony is traditionally described as a tension between intention and literal meaning. Although the concept of sincerity has been discredited by the 20th century theory of literature, it still plays a rather important role in classical scholarship. The paper analyses scholarly discussions about the sincere or ironic nature of Catullus' and Horace's poetry. It investigates characteristic rhetorical formations that make a text able to be read as sincere. Sincerity as well as irony requires the reader's co-operation.
Keywords: Horatius Flaccus, Quintus, 65-8 pr.n.š.; Catullus, Gaius Valerius, ok.84 - ok.54 pr.n.š.; classical philology; klasična filologija; latinska poezija; ironija; iskrenost; retorika; rhetoric